The Interaction Between POMC rs2071345 Polymorphism and Alcohol Dependence in Anxiety Symptoms Among Chinese Male Problem Drinkers - Hong, Liuzhi; Wen, Lutong; Niculescu, Michelle; Zhou, Fan; Zou, Yang; Shen, Guanghui; Wang, Wei; Liu, Yanlong; Chen, Yu-Hsin; Wang, Fan; Chen, Li (Frontiers in Psychiatry, 2022)
Objective: Alcohol dependence can increase the level of anxiety. A growing body of research has identified a link between anxiety symptoms of problem drinkers and their genetic or environment factors respectively. However, to date few studies have directly examined gene-environment (G × E) interaction on their anxiety symptoms during the acute alcohol withdrawal. The present study aims to examine the interaction between the polymorphism of the proopiomelanocortin (POMC) rs2071345 and alcohol dependence on anxiety symptoms of male problem drinkers. Moreover, whether these potential G × E interactions would be consistent with the diathesis stress model versus the differential susceptibility model was tested. Methods: A total of 440 male problem drinkers (Mage = 44.5 years, SD = 9.45) were recruited from nine main psychiatric hospitals of northern China during acute alcohol withdrawal. Blood samples were collected for genotyping, self-reported anxiety symptoms, and levels of alcohol dependence were assessed. Results: Results indicated that the POMC rs2071345 polymorphism significantly moderated anxiety symptoms associated with alcohol dependence. A region of significance (RoS) test showed that male problem drinkers with T allele were more likely to experience more anxiety symptoms than those with CC homozygote when the standardized score of concurrent alcohol dependence was above 0.31. Confirmatory model evaluation indicated that the interaction effect involving POMC gene polymorphism conformed to the diathesis-stress model rather than differential-susceptibility model of person × environment interaction. Conclusions: This study suggested that the SNP in POMC rs2071345 was associated with alcohol dependence in anxiety symptoms of male problem drinker and further provided evidence in support of the diathesis-stress hypothesis of alcohol dependence in terms of anxiety symptoms.